Regulatory Integration of International Capital Markets - Jean-Marie Meier (Oesterreichische Nationalbank (OeNB), 2017)
I examine the financial and real effects of regulatory integration of international capital markets using a unique policy plan by the European Union, which creates a common European market for financial services and capital, through, e.g., passporting rights. For identification, I exploit the bilateral and staggered nature of laws that are passed at the European level but are implemented by national governments. Over its implementation, regulatory integration leads to large increases in external financing, investment and employment for publicly listed firms. These results highlight the importance of regulatory integration of international capital markets for firms' financing decisions and real outcomes.
Keywords: 330; International law; regulation; integration; passporting rights; capital markets; external finance; real effects